On Sperner (semi)hypergroups. (February 2015) - Jafarpour, M.; Aghabozorgi, H.; Leoreanu-Fotea, V.
Abstract: In this paper using Sperner family we introduce and study a new class of (semi)hypergroups that we call the class of Sperner (semi)hypergroups. We characterize strongly Sperner semihypergroups of order 3 and the Sperner Rosenberg hypergroups of order 3.